2006
DOI: 10.1007/s10493-005-5786-2
|View full text |Cite
|
Sign up to set email alerts
|

Life History of Kampimodromus aberrans as a predator of Phytoptus avellanae (Acari: Phytoseiidae, Phytoptidae)

Abstract: The biology of Kampimodromus aberrans (Oudemans), a predator of the big bud mite, Phytoptus avellanae Nalepa, was studied under laboratory conditions. All experiments were conducted on hazelnut leaf discs in an incubator at 25 +/- 1 degrees C, with 16:8 h L:D, at an average daily relative air humidity of 76%. Observations were made twice daily for the immature stages and daily for the adults to determine developmental time, survival and fecundity. The mean developmental time for females was 6.90 days and for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 21 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…The phytoseiid mite Kampimodromus aberrans (Oudemans) is an important biological control agent of several plant-feeding mites such as Eotetranychus carpini (Oudemans) (Duso 1989;Schausberger 1997;Tixier et al 1998Tixier et al , 2006Kreiter et al 2002) and Phytoptus avellanae Nalepa (Ozman-Sullivan 2006). In Greece, it is found on various forest and orchard trees as well as on non-cultivated plants and occasionally on vine (Papadoulis 1993;Koveos unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…The phytoseiid mite Kampimodromus aberrans (Oudemans) is an important biological control agent of several plant-feeding mites such as Eotetranychus carpini (Oudemans) (Duso 1989;Schausberger 1997;Tixier et al 1998Tixier et al , 2006Kreiter et al 2002) and Phytoptus avellanae Nalepa (Ozman-Sullivan 2006). In Greece, it is found on various forest and orchard trees as well as on non-cultivated plants and occasionally on vine (Papadoulis 1993;Koveos unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Estimating life and fecundity tables of the predator and prey are essential to evaluate the efficiency and potentiality of a natural enemy on a definite pest (Gabre et al, 2005;Ozman-Sullivan, 2006;Collier et al, 2007;Reis et al, 2007;Ferrero et al, 2007;Broufas et al, 2007). Our results revealed that at immature stages of P. citri, the net reproductive rate (Ro) and Intrinsic rate of natural increase (rm)of N. californicus showed high values, unlike other stages and the mean generation time of predator showed low value when provided mobile immatures as prey.…”
Section: Resultsmentioning
confidence: 85%
“…Six phytoseiid species were found on Q. cerris leaves (Kolodochka 1978;Miedema 1987;McMurtry & Croft 1997;Duso et al 2004;Ripka 2006;Kabíček 2008;McMurtry et al 2013). K. aberrans was regularly sampled on vines in productive vineyards (Tixier et al 2000), and it is a common and frequently observed phytoseiid species in apple and hazelnut orchards (Ozman-Sullivan 2006;Tixier et al 2014). The abundant occurrence of K. aberrans on the inspected oak trees could indicate that Q. cerris is the favoured host plant for this generalist species.…”
Section: Resultsmentioning
confidence: 99%